THE DISCOURSE OF GENERATIONAL DIFFERENCE IN SELECTED NOVELS OF MAYA ANGELOU AND TERRY MCMILLAN (2014)
African American literature has been predominantly a male-preserve in the task of narrating the experience of slavery and its relics of denigration before the advent of reactionary literature by black female writers. Studies on female-authored African American literary works have concentrated on responding to male-authored representations of the tensions of racism, internal crisis of man-woman relationships and the challenges of empowering the black female character. Little attention has been paid to African American female writings across generations and gender categories. This study, therefore, investigates the narrative thrusts of selected works of Maya Angelou and Terry McMillan to determine the dimensions of divergence across generations of African American female writers. The study adopts Alice Walker‘s womanist theory and bell hooks‘ feminist theory which account for differences in the construction of black women consciousness. Six novels – Maya Angelou‘s I Know Why the Caged Bird Sings (1970), Gather Together in my Name (1974), and The Heart of a Woman (1981), and Terry McMillan‘s Waiting to Exhale (1992), A Day Late and a Dollar Short (2001) and The Interruption of Everything (2005) – were purposively selected. The texts are subjected to literary and comparative analyses. From the first autobiography I Know Why the Caged Bird Sings to the last The Heart of a Woman, Angelou offers detailed testimony on the effects of displacement on the individual psyche and the black community. Maya Angelou‘s selected novels reveal the creation of a collective communal memory through the use of the autobiographical prose form. Angelou‘s narratives reveal her understanding of history, her reverence for memory of collective black folk tradition and represent the Black Arts era. In contrast, Terry McMillan‘s Waiting to Exhale, A Day Late and a Dollar Short and The Interruption of Everything reveal a paradigm shift from the communal experience to the individual, the internal crisis among individuals in the family and aspiration of specific sentiments as she projects the female character as ambitious and daring. McMillan‘s fiction stands out in several ways. She revises and borrows recognisable literary conventions to project the changing roles of women to reinforce her radical perspective. However, the choice of professionally successful black women as characters in her novels relates to the drastic increase in the population of working class women in the 1990s and reflexive of the post-womanist tradition. Her works accentuate the quest for personal liberty, romance and intimate relationships as the central conflicts facing black female protagonists. Although two decades separate Angelou‘s I Know Why the Caged Bird Sings and Terry McMillan‘s Waiting to Exhale, a close reading of the novels reveals that the texts derive qualitative interpretations from the unique difference in ideas and aesthetics represented by Alice Walker, bell hooks and other Black feminists. While Maya Angelou‘s novels keep within the womanist tradition, those by Terry McMillan are radically feminist and modernist in orientation. Thus, the two writers exemplify the Black Arts era and post-womanist literary generation respectively and differently situate the novels within specific historical, socio-political, economic, gendered and literary contexts. Key words: Generational difference, Womanism, African American literature, Maya Angelou, Terry McMillan. Word count: 498